The relationship between Marcel Proust and Joseph Babinski: the encounter of two geniuses - José Luiz Pedroso; Orlando G. P. Barsottini; Hélio A. G. Teive; Francisco Cardoso (Arquivos de Neuro-Psiquiatria)
Marcel Proust was one of the greatest French writers of all times. Since early in his life, Proust was interested in arts and particularly literature. He also demonstrated a great knowledge of medicine, particularly neurology. His father was a doctor, and contributed to neurology through studies on aphasia, stroke, hysteria, and neurasthenia. During his childhood, Proust had the first asthma attack, initially considered a manifestation of neurasthenia. Regarding his illness, Proust was in touch with several renowned neurologists, such as Brissaud, Babinski and Sollier, and other disciples of Charcot. Proust spent the last three years of his life mostly confined to his bedroom since his health had badly deteriorated. In one moment, Babinski was called, examined Proust and after leaving his bedroom, announced to his brother that Proust was practically dead. Few hours later, Proust developed vomica and died.